2001
DOI: 10.1046/j.1440-1843.2001.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic bronchitis and chronic respiratory symptoms in adults over the age of 35 years in Isfahan, Iran in 1998

Abstract: Obstructive airway diseases are under-diagnosed in developing countries. Physicians practising in such areas of the world should be aware, and try to detect the subclinical illnesses, especially in urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…A comparison of the two national health surveys conducted in 1991 and 1999 revealed an increase in the prevalence of waterpipe smoking (from 0.8 to 1.4%) among Iranian adolescents [18] . Considering the prevalence of cigarette smoking in Iranian women, which is 1.2% in rural [19] and 3.6% in urban areas [20] , the prevalence of waterpipe smoking seems to be roughly 7 times higher than that of cigarette smoking, indicating a preference of Iranian women for waterpipe smoking, thereby confirming societal acceptance of women smoking waterpipe [21] . It is noteworthy that the exclusion of cigarette smokers is likely to underestimate the prevalence of waterpipe use since some of them smoke both cigarettes and waterpipe.…”
Section: Discussionmentioning
confidence: 87%
“…A comparison of the two national health surveys conducted in 1991 and 1999 revealed an increase in the prevalence of waterpipe smoking (from 0.8 to 1.4%) among Iranian adolescents [18] . Considering the prevalence of cigarette smoking in Iranian women, which is 1.2% in rural [19] and 3.6% in urban areas [20] , the prevalence of waterpipe smoking seems to be roughly 7 times higher than that of cigarette smoking, indicating a preference of Iranian women for waterpipe smoking, thereby confirming societal acceptance of women smoking waterpipe [21] . It is noteworthy that the exclusion of cigarette smokers is likely to underestimate the prevalence of waterpipe use since some of them smoke both cigarettes and waterpipe.…”
Section: Discussionmentioning
confidence: 87%
“…The causes of this phenomenon might be related to the increased air pollution both from traffic sources and industries. 9,10 The findings of a meta-analysis in Iran showed that the prevalence of CB was 5.6%. However, in the present study, the prevalence of CB among Khameneh adults was found to be 2.4% based on clinical symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…6,8 Various reports have been received from different parts of Iran on the prevalence of CB. For example, in the study of Golshan and colleagues conducted in 2001, the prevalence of CB was 4.66%, 9 but in another study conducted in 2011, the prevalence was increased to 8.18%. 10 Moreover, in a study in Tehran, the prevalence of CB was reported high (10.9%), 11 while in the study of Amra and Hashemiin Shahrekord, the prevalence was reported low (1.8%).…”
Section: Introductionmentioning
confidence: 96%
“…Cigarette smoking is not a widely popular habit in Isfahan; 16,17 therefore, one would expect a lower prevalence of chronic respiratory disorders in rural areas of this city.…”
Section: Introductionmentioning
confidence: 98%
“…Only limited information is available concerning the epidemiology of chronic obstructive disorders in developing countries of the Middle East. 15 Cigarette smoking is not a widely popular habit in Isfahan; 16,17 therefore, one would expect a lower prevalence of chronic respiratory disorders in rural areas of this city.…”
mentioning
confidence: 99%